Developmental Differences in Prosocial Behavior Between Preschool and Late Elementary School - Flook, Lisa; Zahn-Waxler, Carolyn; Davidson, Richard J. (Frontiers in Psychology, 2019)
Research points to evidence of innate prosocial tendencies present early in life. As more complex cognitive abilities emerge with development, this may alter the expression and nature of prosocial behaviors over time. Sharing behavior is one important aspect of prosocial behavior. Our aim was to explore how children’s sharing behavior with different recipients across important social categories changes by comparing two distinct transitional periods in development. We compared the responses of 46 preschoolers (M age=4.95) and 52 5th graders (M age=9.98) on two social decision-making paradigms. Results showed that older children shared more selectively depending on the recipient (e.g., 5th graders shared more with a child who was sick than with a least liked child) than younger children, who shared resources more equitably with different recipients. A second paradigm revealed greater uncoupling of behavior and cognition among older children, such that prosocial behavior in preschoolers was more closely linked to their judgments about the recipient’s character than it was for 5th graders. A greater capacity for perspective taking and cognitive complexity that emerges over the course of development can be used to help or discriminate against others, depending upon how those capacities are channeled. Therefore, how these abilities are shaped has important societal consequences.